HOSPITAL MANAGEMENT'S ACCOUNTABILITY FOR ACCIDENT VICTIMS IN SERVICE EMERGENCY - Ady Purwoto (International Journal of Health Science & Medical Research, 2022)
The victim of a traffic accident is one of the patients who need immediate medical treatment to avoid disability or death. Law No. 36 of 2009 concerning Health states that the obligation for every health service facility, both government and private, has an obligation to provide health services for the rescue and prevention of further disabilities. Emergency services risk a person's survival. Therefore from a juridical point of view, there are some exceptions that are different from ordinary circumstances. The novelty of this study is that it examines the Responsibility of Hospital Management toward Accident Victims in Emergency Services. This study aims to determine and analyze the fulfillment of the rights of accident victims and the responsibility of hospital management to accident victims in emergency services. This type of research is normative juridical legal research with descriptive research methods. The data secondary data used consists of primary legal materials, secondary legal materials, and tertiary legal materials. Data collection through literature studies. After the data is obtained, the data is then processed by means of data inspection, editing, and systematic data, which is then analyzed descriptively and qualitatively. The results of this study show that the fulfillment of the rights of accident victims in emergency services at the hospital is in accordance with laws and regulations. This is evidenced by the fulfillment of patient rights, including no discriminatory treatment and not asking for a down payment for patients with emergency situations. The conclusion of this study is that the responsibility of hospital management for handling accident victims in emergency services has been fulfilled by providing human resources and facilities in accordance with applicable laws and regulations. Keywords: Accountability; Emergency Services